Krytyka literacka po 1989 roku wobec klasycyzmu - Woźniak-Łabieniec, Marzena (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2009)
The aim of the article is present the controversy in review of literature on a subject classicism after 1989. Different sense (methods) of reason this term influenses classification of poetry. Besides one of important aim of review is designation differences beetwen classicism and postmodernism. The difficulty is that modern classicism is changing and developing. We researched it in statu nascendi.